An investigation of transonic flow over axisymmetric rigid body - Tuerkyilmaz, Ibrahim (Computers & fluids, 2010)
The aim of this study is to investigate transonic flow over the axisymmetric rigid body of revolutions using matched asymptotic expansions of high Reynolds number flow. For this purpose the triple-deck model is employed. It allows to study the flow separation near a junction line where a circular cylinder is connected to a divergent conical body. It is found that in the axisymmetric transonic flow the interaction region is governed by the viscous–inviscid interaction process, where the axisymmetric Karman–Guderley equation in the inviscid part of the flow should be coupled with Prandtl’s boundary layer equations for the viscous sublayer. The coupled governing equations of the interaction region is solved using a semi-direct numerical method considering proper boundary conditions. Numerical results imply that incipience of separation may appear over the axisymmetric rigid body subject to body shape and transonic axisymmetric nature makes the flow much less prone to separation as compared to the two-dimensional flow.